Quantification of Total Biomass and Carbon Stock in Oil Palm Plantations Based on Compartments: Main Stand and Understory Vegetation - Al-faruq, Khoirul Ummah; Yuniasih, Betti; Noviyanto, Amir (Jurnal Biologi Tropis, 2026)
Oil palm plantations play a role in carbon storage; however, field-based information on biomass and carbon stock distribution among vegetation compartments remains limited. This study aimed to estimate biomass and carbon stocks of oil palm plantations based on main stand components and understory vegetation across immature (TBM), prime mature (TM Prime), and old mature (TM Old) growth phases. Field measurements were conducted in Central Kalimantan using plot sampling with a planting density of approximately 143 trees ha⁻¹. Main stand biomass was estimated non-destructively using compartment-based allometric equations, while understory biomass was measured destructively. The results showed an increase in biomass from approximately 94 kg tree⁻¹ at the TBM stage to 486–517 kg tree⁻¹ at the TM Prime stage and 495–582 kg tree⁻¹ at the TM Old stage, following a sigmoid growth pattern. Carbon stock was predominantly contributed by the oil palm main stand (5290.59 t C ha⁻¹), whereas understory vegetation contributed only a minor proportion (0.247 t C ha⁻¹). These findings provide transparent empirical data to support greenhouse gas accounting within the Indonesian Sustainable Palm Oil (ISPO) framework.